O visível e o invisível na cultura cigana: a (in)visibilidade social voluntária na escola - Rodrigues, Maria Lúcia (2025)
This study investigates the relationship between gypsy culture and school spaces, focusing on Trindade-GO, where there is a significant gypsy community. Although gypsy communities are part of Brazil's cultural diversity, they often move in an "invisible" way in social and educational spaces. The research is based on evidence of the systematic concealment of gypsy culture in educational institutions, despite documents such as the BNCC and the PCNs addressing cultural diversity - a paradox that casts a "cloak of invisibility" over gypsies. The main objective is to verify how the social invisibility of gypsies manifests itself in the school space, analyzing whether it is socially imposed or constitutes a strategy for preserving identity. The research questions: Is there a "voluntary (in)visibility" of gypsies? Do schools provide equity to invisible cultures? Is institutional silence due to lack of knowledge or structural factors? Based on the concepts of social invisibility of Axel Honneth (2001) and the works of Sá Pinto Tomás (2008), the research also mobilizes specific studies on gypsy communities through Fazito (2006), Siqueira (2007), Simões (2007) and others. Methodologically, the study adopts a qualitative approach combining ethnographic research in schools, collection of narratives, bibliographic study and comparative analysis. The central hypotheses include: there is a dynamic interplay between social visibility and invisibility of gypsies; due to discrimination, gypsies strategically choose invisibility in certain situations; the community studied, composed of Brazilians of gypsy descent, has two native cultures and adapts to the hegemonic one in a process of "accommodating assimilation"; this phenomenon is reproduced in the school environment, harming the educational performance of young gypsies. The study concludes that the intentional concealment of gypsy identity in the school context is related to the protection of an identity that the student believes will not be valued. Gypsy identity emerges mainly in "closed moments" among peers, while in public spaces, Gypsies often "camouflage themselves" to interact with non-Gypsies. Thus, Gypsy resistance – whether as "accommodating assimilation" or "voluntary social (in)visibility" – reflects an ongoing struggle for identity preservation in the face of centuries of oppression and marginalization.